The relationship of training load and acute: chronic workload ratio in professional karate athletes - Yu, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: ACWR (acute: chronic workload ratio) was regarded as a valid parameter for predict injury. Calculating the ACWR of RPE (rate of perceive exertion) has been used to monitoring training in sports such as karate. Previous studies investigate the relationship between ACWR and injury risk/injury rate, which shown certain reliability and validity. However, the relationship between ACWR and other load related parameters are unknown. This study aims to investigate the relationship between ACWR and different training session load as well as daily and weekly training load. METHODS: 11 professional karate athletes (Age 22.7±2.1 years, Height 169.9±8.7 cm, Weight 63.6±10.9 kg, Training History 5.5±2.4 years) participated in this study. The training session includes strength & conditioning (S&C) and technical training. S&C were the same for both kata and kumite, while the technical training program were different. Athletes were required to send their RPE on the phone through a questionnaire collection software within 30 minutes after every session of each training day. Foster modified CR-10 RPE scale was used [1]. RPE of each session is sRPE. Training load (A.U.=Arbitrary Units) is the product of sRPE and training time (hours). Training load of each session was calculated. Weekly training load (the sum of one week`s total training load), ACWR (the ratio between the average daily load of the most recent 1 week and the average daily load of the most recent 4 weeks) and average daily training load (Total weekly training load divided by training days per week) were collected. Data of 226 weeks of all athletes were analyzed. Using multiple linear regression to investigate the relationship between ACWR and other parameters, with S&C training load, technical training load, weekly total training load and average daily training load as independent variables and ACWR as dependent variables. Significant difference was set at P